Means, Methods and Use of ICT for the Formation of Technological Competencies of Students in Schools - Fattayevna, Xolmirzayeva Dilaferuz; Baxramovna, Turg’unova Umidaxon (European Journal of Life Safety and Stability (2660-9630), 2021)
The active introduction of information and communication technologies in the field of education is, therefore, a distinctive feature of modernity. Important pedagogical tasks that are solved as a result of the use of such technologies are: the development of up-to-date information, the expansion of the information sphere of education, the creation of an information and educational space in an educational institution, the introduction of distance learning technology into pedagogical practice, the rationalization of the educational process, the activation of educational activities, the development of a culture of independent, research activities of students and, in general, improving its effectiveness and quality.